MEDIA AUGMENTED REALITY BERBASIS ANDROID DALAM MATERI BANGUN RUANG SISI DATAR SISWA SMP - Ningtias, Ayu; Hartoyo, Agung; Suratman, Dede (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to: (1) Produce a decent learning media in  application using Augmented Reality technology based on android of Polyhedron subject and (2) Know student motivation after using the media. This research used Research and Design (R & D) methode. The subjects were VIII I Junior High School 3 Pontianak, include by 37 students. The stages of this research include by  analysis, design, development, implementation and evaluation. The result of this research was the media has been categorized as "very feasible" and the category of validity was "very valid". However, there was a revision by the media and material expert . There were an addition of the usage menu, the setting of  AR camera distance to the marker and the video should be made relevant to the polyhedron subject. Motivation by 37 students of SMP Negeri 3 Pontianak after using the developed product increased from 14 students were categorized very low motivation,10 students in  low motivation, 7 students in high motivation, and 7 in  very high motivation become22 students were categorized high motivation and 15 students in very high motivation. By the result of this research, students motivation was increased after using the geometry learning media using Augmented Reality technology based on Android in Polyhedron subject. Keywords: Augmented Reality, Student’s Motivation , Feasibilty of Media, Polyhedron Subject